A seroepidemiological survey of adenovirus type 7 circulation among healthy adults in China and in Sierra Leone, West Africa - Wang, Busen; Li, Jianhua; Wu, Shipo; Wang, Yudong; Chen, Yi; Zhai, Yanfang; Song, Xiaohong; Zhao, Zhenghao; Zhang, Zhe; Zhang, Jinlong; Yu, Rui; Hou, Lihua; et al. (Frontiers in Public Health, 2023)
Adenovirus type 7 (HAdV7) is one of the most pathogenic human adenoviruses (HAdVs) and can cause severe illness and even death, particularly in people with weakened immune systems. Many countries worldwide have experienced epidemics of this highly contagious pathogen, including China and Sierra Leone; however, studies describing the seroprevalence of anti-HAdV7 neutralizing antibodies (nAbs) are still lacking. Herein, we established an efficient neutralization assay based on a recombinant luciferase-expressing HAdV7 virus (HAd7-Luc) to monitor historical HAdV7 infections and predict outbreak distributions. Among the 2,350 serum samples collected from eight sites in China and Sierra Leone in this cross-sectional serological survey, the overall proportion of anti-HAdV7-seropositive individuals was nearly 60%, with higher seroprevalence rates in Sierra Leone than in China. Regionally, HAdV7 nAb titers were higher in China than in Sierra Leone and showed a geographic variation across different regions. Regardless of the location, the seropositive rate of HAdV7 nAb was lower than that of HAdV5 nAb, as was the nAb titer. The prevalence rates of antibodies against HAdV7 and HAdV5 were both related to age but not to sex. In addition, serologic cross-reactions were rarely observed among people infected with HAdV7 and HAdV5. These results indicate a humoral immune response acquired through endemic HAdV7 infection and enrich the understanding of not only the epidemiological prevention and control of HAdV7 but also the clinical application of HAdV7-based vaccines or gene therapy tools.